Molecular cloning and nucleotide sequences of the complementary DNAs to chicken skeletal muscle myosin two alkali light chain mRNAs. - Nabeshima, Y (1982)
We report here the molecular cloning and sequence analysis of DNAs complementary to mRNAs for myosin alkali light chain of chicken embryo and adult leg skeletal muscle. pSMA2-1 contained an 818 base-pair insert that includes the entire coding region and 5' and 3' untranslated regions of A2 mRNA. pSMA1-1 contained a 848 base-pair insert that included the 3' untranslated region and almost all of the coding region except for the N-terminal 13 amino acid residues of the A1 light chain. The 741 nucleotide sequences of A1 and A2 mRNAs corresponding to C-terminal 141 amino acid residues and 3' untranslated regions were identical. The 5' terminal nucleotide sequences corresponding to N-terminal 35 amino acid residues of A1 chain were quite different from the sequences corresponding to N-terminal 8 amino acid residues and of the 5' untranslated region of A2 mRNA. These findings are discussed in relation to the structures of the genes for A1 and A2 mRNA.